2018
DOI: 10.1111/are.13842
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two novel peritrophic membrane (PM) genes in the Chinese mitten crab Eriocheir sinensis that exhibit activity against high-pH stress and Aeromonas hydrophila challenge

Abstract: The peritrophic membrane (PM) is located in the gut of most insects and protects them from invasion by pathogens or toxins ingested during feeding. Peritrophins are a principal component of the PM and contribute to the structure and function of the PM. The PM has also been observed in the gastrointestinal tract of the Chinese mitten crab (Eriocheir sinensis). In this study, full‐length cDNA sequences of two PM genes from E. sinensis were obtained, namely, Es‐peritrophin1 and Es‐peritrophin2, which were 855 bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Furthermore, characterized C. rogercresseyi peritrophins presented two or three ChBD2s. Similar results have been reported in crustacean species, Fenneropenaeus Chinensis , P. monodon , Penaeus semisulcatus, and E. sinensis [ 44 , 50 , 51 ]. In addition, more than three ChBD2 domains have been described for insect peritrophins [ 77 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, characterized C. rogercresseyi peritrophins presented two or three ChBD2s. Similar results have been reported in crustacean species, Fenneropenaeus Chinensis , P. monodon , Penaeus semisulcatus, and E. sinensis [ 44 , 50 , 51 ]. In addition, more than three ChBD2 domains have been described for insect peritrophins [ 77 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Chinese mitten crab Eriocheir sinensis has the Es-peritrophin1 whit a MW of 28.93 KDa. However, for this crab was also reported the Es-peritrophin2 with 51.17 KDa [ 50 ]. Additionally, the pI found in the peritrophin-like proteins of C. rogercresseyi were in a range between 4.5 and 6, which is common among other peritrophins [ 39 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The PM was believed to protect the gut epithelia, facilitate digestion (Agrawal et al, ) and neutralize ingested toxic compounds found in plants (Zhao et al, ). Our previous studies showed the expression of PM genes, Es‐PL44 (Gen Bank accession number: ) and Es‐PP1 (Gen Bank accession number: ), that are involved in the structure and digestive function of PM in hindgut of Chinese mitten crab (Li et al, ) exhibit activity against high pH stress and Aeromonas hydrophila challenge (Wang et al, ) and were modulated by diet ingredients (Ren et al, in press).…”
Section: Introductionmentioning
confidence: 99%